Gaya Kepemimpinan Perempuan dalam Jabatan Publik : Studi Kasus pada Kantor Dinas Kesehatan Kota Surakarta - Rani Kasih Setianingsih; Cicilia Dyah S I; Susantiningrum Susantiningrum (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The aims of this research are To find out the leadership style of women in the Surakarta City Health Office,To find out the role of women leaders based on leadership style in public office, To find out the challenges of women leaders in public office. This research uses a qualitative research method with a case study approach. The source of this research is the actions and habits of the Head of the Surakarta City Health Service, which were obtained through observations of the work environment of the Surakarta Health Service, in-depth interviews with various related sources, and documentation from biographies and social media. The validity test used to test the validity of this research uses triangulation of methods and data sources. The results of this research are as follows. First, the Head of the Surakarta Health Service has various elements of leadership style, including feminine, masculine, transformational, and transactional leadership styles. This can be seen from his actions and policies in leading the agency. These results explain that there is no relationship between gender and the choice of leadership style. Second, the Head of the Surakarta Health Service has a big role in motivation and is also a good role model for the agency, so the Surakarta Health Service becomes the best agency in the Surakarta City government. Third, as a woman, the Head of the Surakarta City Health Service does not experience problems or obstacles caused by gender differences. These results show no differences in the challenges faced by men or women.